MELT PERCOLATION IN A PARTIALLY MOLTEN MANTLE MUSH: EFFECT OF A VARIABLE VISCOSITY - Khodakovskii G.; Rabinowicz M.; Ceuleneer G.; Trubitsyn V.P. (My University, 1995)
Data collected in ophiolite massifs indicate that some horizons with very high melt fractions have been frozen during the accretion of the harzburgites just below the crust. We show that the existence, distribution and amplitude of these impregnations are better understood if rheological bifurcations due to the increase in melt fraction, in addition to a power-law dependence of permeability on porosity, are taken into account in the compaction models. As shown by deformation experiments on partially molten rock, at melt fractions of around 5–10% a first rheological bifurcation occurs when the melt wets the grain boundaries of mantle minerals, enhancing diffusion processes. A second one occurs when the melt fraction exceeds the second percolation threshold (around 25–30%). Our 1D numerical experiments based on the compaction equations integrating the effect of these bifurcations show striking features reminicent of observations in ophiolites.